1997
DOI: 10.3109/09638289709166547
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between use of technology and employment rates for people with physical disabilities in Australia: Implications for education and training programmes

Abstract: This study examined the impact of computer and assistive device use on the employment status and vocational modes of people with physical disabilities in Australia. A survey was distributed to people over 15 years in age with physical disabilities living in the Brisbane area. Responses were received from 82 people, including those with spinal cord injuries, cerebral palsy and muscular dystrophy. Of respondents 46 were employed, 22 were unemployed, and 12 were either students or undertaking voluntary work. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Twelve investigated age as a continuous correlate, with 8 of these studies 14-21 finding a one-year increase in age was associated with a 2-4% decrease in odds of employment. Three studies [22][23][24] found no significant difference in odds of employment based on age. Three studies 8,25,26 investigated age as a dichotomous correlate, with two studies finding no significant difference in odds of employment between age groups and one finding a significant decrease in the likelihood of employment for those older than 55 years.…”
Section: Non-modifiable Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Twelve investigated age as a continuous correlate, with 8 of these studies 14-21 finding a one-year increase in age was associated with a 2-4% decrease in odds of employment. Three studies [22][23][24] found no significant difference in odds of employment based on age. Three studies 8,25,26 investigated age as a dichotomous correlate, with two studies finding no significant difference in odds of employment between age groups and one finding a significant decrease in the likelihood of employment for those older than 55 years.…”
Section: Non-modifiable Factorsmentioning
confidence: 97%
“…Twenty-one studies investigated sex as a correlate of employment, with ten 15,19,23,24,[26][27][28][29][30][31] finding no significant difference between males and females. Eleven studies 8,17,18,21,25,[32][33][34][35][36]42 found a significant difference in odds of employment based on sex, with eight finding higher odds in males.…”
Section: Non-modifiable Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Fewer again are reported as being currently employed (13% to 56%), 14,15 highlighting that once a position is secured in the workforce, further problems may be experienced in sustaining employment. In terms of the types of occupations in which people are likely to be employed post-SCI, a substantial proportion ®nd jobs in clerical or data entry areas, with fewer people employed in professional or managerial positions.…”
Section: Introductionmentioning
confidence: 99%